1856 Ky. Acts 139 - (:unkn) unknown (My University, 1855)
An Act to Incorporate the Town of Baltimore, Hickman County, ch. 475,§ 10: Any person who shall shoot off a gun or pistol, or shall run or gallop a horse creature in said town, shall be liable to a fine of not less than two nor more than four dollars
Keywords: DISCHARGE